DIGITALISASI FILANTROPI ISLAM PADA PESANTREN DI PULAU MADURA - Firman Ardiansyah; Fitriyana Agustin; Ridan Muhtadi (Program Studi Perbankan Syariah STAI Al-Fitrah Surabaya, 2021)
The Islamic financial literacy and inclusion index in Indonesia is still relatively low. Based on data from the Financial Services Authority (OJK) in 2019 shows that the level of Islamic financial literacy is only around 8.93% and the level of Islamic financial inclusion just only around 9.1%. The low of public access to the banking will be quickly resolved by combining financial services and products using the latest technology. These efforts needs to be made, because the 5.0 industrial revolution makes it easier for people to access all information using smartphones that are connected to the internet. This decision will be a great opportunity for the Islamic finance industry to innovate digitally. The author offers digital innovation to accommodate these opportunities through the “CONTREN: (Connected Sharia Economic of Pesantren)” application which focuses on ZISWAF transactions (Zakat, Infaq, Shadaqah, Waqf) equipped with supporting features that can be enjoyed by all groups of people. The main purpose of writing this scientific paper is to analyze the normative picture of the potential for digitizing Islamic philanthropy in Madura. This study uses a descriptive qualitative method that explains the suitability of the features in the